The Relationship of Food Consumption and Nutritional Status on Employee of Health Polytechnic Directorate Health Ministry Medan - Aritonang, Evawany; Sari Siregar, Emi Inayah; Nasution, Ernawati (International Journal on Advanced Science, Engineering and Information Technology, 2016)
The increasing prevalence of overweight can be seen from the people who are overweight and obesity. North Sumatera is one of the provinces which has the higher prevalence of overweight and obesity than the national rate at 13% and 18.1%. One of the factors associated with overweight and obesity is food consumption. Poor dietary habbit, which is low in fiber and high in fat, can lead to weight gain. The purpose of this study was to determine the relationship of dietary habbit to nutritional status. The research used cross sectional design. The sample were 70 employee of Health Polytechnic Directorate, Health Ministry of Medan and taken by using total sampling technique. The measured factors were carbohydrate and fat intake, the type of food and nutritional status. The data were obtained based on the interviews using food recall, FFQ and questionnaires and measurement of IMT. Data were analyzed using chi square test. The results showed that there was a relationship between the adequate intake of carbohydrates (p = <0.001) and adequate intake of fat (p = 0.022) to nutritional status while the type of food consumed does not show relationship to nutritional status. It is recommended that The Management of Health Polytechnic Directorate, Health Ministry, Medan to do concealing, make policy and supervision to carry out